Closure to the discussion on "The effect of double stratification on boundary-layer flow and heat transfer of nanofluid over a vertical plate" [Comput. Fluids 86 (2013) 433–441] and on "Hydromagnetic bioconvection of nanofluid over a permeable vertical plate due to gyrostatic microorganisms" [Comput. Fluids 95 (2014) 88–97]. (21st December 2015) - Makinde, O.D.; Ibrahim, W.
Highlights: Ibrahim and Makinde 2013 dimensionless model equations and results are correct. Mutuku and Makinde 2014 dimensionless model equations and results are correct. Minor typo-misprints in the two published articles are corrected. Abstract: In this paper, we present the closure to the comments made by Pantokratoras [Comput. Fluids 109 (2015) 185] on "The effect of double stratification on boundary-layer flow and heat transfer of nanofluid over a vertical plate" [Comput. Fluids 86 (2013) 433–441] and on "Hydromagnetic bioconvection of nanofluid over a permeable vertical plate due to gyrostatic microorganisms" [Comput. Fluids 95 (2014) 88–97] and upholds the mathematical correctness of the results in the two published articles.